Enhancing Chemical Management Practices and Waste Efficiency: A Survey on Awareness Among UTHM Students and Staff - Zakaria, Nor Hanani; Ismail, Shuhaida (Enhanced Knowledge in Sciences and Technology, 2024)
The environment and public health are seriously threatened by chemical waste, which is a major concern. With an emphasis on comprehending the knowledge, practices, and safety precautions amongUniversity Tun Hussein Onn Malaysia (UTHM) students who have hands-on experience with laboratory systems, this study aims to evaluate laboratory safety in the context of chemical exposure. The survey's results show that participants have an acceptable level of awareness, and most of them indicate that they would like to learn more about handling chemicals. The results highlight the need for focused treatments that take into account each person's unique proficiency level as well as the connectivity of waste reduction efforts. Organisations are urged to put in place comprehensive training programmes in order to achieve the goal of thoroughly analysing chemical safety and awareness for reducing chemical waste. Additionally, encouraging a comprehensive approach to chemical safety can help to create wasteand environmentally-conscious work environments. Organisations may play a major role in reducing chemical waste, safeguarding human health, and protecting the environment by adopting sustainable practices and cultivating a culture of continuous learning.